Rancang Bangun Sistem Informasi Helpdesk Ticketing Berbasis Web pada PT. Mitra Tiga Berlian Bekasi - Lia Mazia; Lilyani Asri Utami; Feby Karina Bintang (Teknik Informatika Universitas Pamulang, 2021)
In company activities, the IT helpdesk plays an important role in ensuring and providing the best quality related to information technology. When carrying out work activities that use information technology, there are problems that arise in the use of IT, including at PT. Mitra Tiga Berlian (MTB). MTB is a company engaged in the service sector, to be precise a car service workshop (body repair and oven painting specialist) located on Jl. Kalimanggis, Jatikarya, Bekasi. In designing the IT helpdesk information system on MTB, the authors conducted observations and interviews beforehand designing a web-based information system using the waterfall method so that the system designed can be used by the IT department in problem reports quickly and can store information on the problem of each problem in the complaint. that occurs, thus minimizing communication errors in the IT Helpdesk.